METHODOLOGY OF EDUCATION IN THE SPIRIT OF MILITARY PATRIOTISM IN THE PROCESS OF EDUCATION - Sotvoldiev Abdulhoshim Yuldashovich; Kobilov Nozimzhon Mingboyevich (Scholar Express Journal, 2022)
In the article, the relevance of the issue of educating young people in the spirit of patriotism, the fact that education in the spirit of military patriotism is at the center of state policy in the educational process, the important aspects of the reforms being carried out in this regard, and the importance of educating young people in the spirit of military patriotism in the process of globalization traditional and modern methods of education are covered
Keywords: methodology; military patriotism; youth; reforms; action strategy